Amplitude of Low-Frequency Fluctuation With Different Clinical Outcomes in Patients With Generalized Tonic–Clonic Seizures - Zu, Meidan; Fu, Lulan; Hu, Mingwei; Cao, Xiaoyan; Wang, Long; Zhang, Juan; Deng, Ziru; Qiu, Bensheng; Wang, Yu (Frontiers in Psychiatry, 2022)
Background: Primary generalized tonic-clonic seizures (pGTCS) are associated with significant disability and sudden unexpected death when they cannot be controlled. we aimed to explore the underlying neural substrate of the different responses to antiseizure drugs between the seizure-free (SF) and non-seizure-free (NSF) patients with pGTCS through amplitude of low frequency fluctuation (ALFF) method. Methods: We calculated ALFF among the SF group, NSF group and healthy controls (HCs) by collecting resting-state functional magnetic resonance imaging (rs-fMRI) data. One-way ANOVA was used to compare ALFF of the three groups and post-hoc analysis was done at the same time. Pearson’s correlation analysis between ALFF in the discrepant brain areas and the clinical characteristics (course of disease and age of onset of pGTCS) was calculated after then. Results: Significant group effect was found in the right fusiform gyrus (R.FG), left fusiform gyrus (L.FG), left middle occipital gyrus (L.MOG), right inferior frontal gyrus (R.IFG), right precentral gyrus (R.PreG), right postcentral gyrus (R.PostG) and left calcarine sulcus (L.CS). The SF and NSF groups both showed increased ALFF in all discrepant brain areas compared to HCs except the R.IFG in the NSF group. Significantly, higher ALFF in the bilateral FG and lower ALFF in the R.IFG were found in the NSF group compared to the SF group. In addition, two positive correlations were observed between ALFF in the bilateral FG and course of disease in the SF group. Conclusions: Higher ALFF in the bilateral FG were found in the NSF group compared to the SF and HCs groups. Our findings indicate that abnormal brain activity in the FG may be one potential neural substrate to interpret the failure of seizure control in patients with pGTCS.